Mechanical properties of glass fiber and liquid crystalline polymer reinforced polypropylene hybrid composites toughened with elastomers - Tjong, S. C.; Xu, S. A. (Journal of applied polymer science, 2004)
A group of short glass fiber (SGF) and liquid crystalline polymer (LCP) reinforced polypropylene (PP) hybrid composites and toughened with maleic anhydride (MA)‐grafted styrene–ethylene butylene–styrene (SEBS‐g‐MA) elastomers with controlled morphology were designed and injection molded. MA was also grafted to PP (PP‐g‐MA) in which the mPP blend was prepared by compounding 95% PP and 5% PP‐g‐MA. The matrix of hybrid composites consisted of 80/20 (wt %) mPP/SEBS‐g‐MA. The fibrillation of LCP minor phase depended on the injection‐molded temperatures. The effects of LCP and SGF hybridization on the morphology and mechanical characteristics of quaternary hybrid composites were studied. Tensile measurements showed that hybridization of SGF and LCP fibrils were beneficial in improving the tensile strength and stiffness of hybrid composites prepared at 265 and 285°C. This was attributed to the fact that LCP minor phase can deform into fine and long fibrils at these temperatures. However, LCP minor phase was deformed to nonuniform ellipsoids at 220°C, leading to poorer mechanical performance of the hybrid composites. The correlation between the processing temperature and compatibilizer with the structure–mechanical property of hybrid composites is discussed. © 2004 Wiley Periodicals, Inc. J Appl Polym Sci 94: 1539–1546, 2004